Impactos na agricultura brasileira utilizando diferentes cenários de demanda doméstica de etanol - Wanderson Santos Costa; Heloísa Musetti Ruivo; Aline Cristina Soterroni; Fernando Manuel Ramos; Fabiano Mezadre Pompermayer (Instituto de Pesquisa Econômica Aplicada (IPEA), 2025)
– This work evaluates the effects on land use in agricultural and forestry activities in terms of a hypothetical scenario of reducing Brazilian domestic demand for fuel ethanol to zero. For this purpose, we use the Globiom-Brazil model, which simulates the producers' decision on which activity to develop considering input costs, product sales prices, land productivity, and marketing and transport costs, in a spatial price equilibrium model with 30 regions distributed around the world, with spatial detailing of Brazil in cells of about 50 x 50 km. The scenarios take into account the illegal deforestation control, climate change impacts on the main crops, and demand projections aligned with the socioeconomic narrative SSP2. The scenarios differ only in terms of domestic demand for fuel ethanol: in the Baseline scenario, demand grows according to the historical trends until 2030, remaining constant from then until 2050, the final year of the projection; the Zero Ethanol scenario maintains the historical trends until 2025 when it starts to decrease monotonically until reaching zero in 2050. The results indicate that the sugarcane area in the Zero Ethanol scenario would suffer a loss of 8.68 Mha in 2050 compared to Baseline. Within this area, 2.02 Mha would be allocated to other crops, 2.58 Mha to livestock, 0.82 Mha to native vegetation, and 3.20 Mha to non-productive areas. The producers' aggregate economic return would be reduced in almost all years of the projection, with the loss of income from sugarcane not being compensated by the profits in the other modelled activities. However, the return on other activities would be greater than the loss caused by lower sugarcane production by 2050.
Keywords: R11; R12; Q1; Q16; 330; land use model; biofuels